Music of the middle ages: style and structure - Wilson, David Fenwick (New York Schirmer books (Macmillan), 1990)
Music of the Middle Ages provides a comprehensive, chronological survey of musical style and compositional technique from early plainchant to the flushing of fourteenth century polyphony.